NPK NUTRIENT STATUS IN SOIL AND LEAVES OF PIPER NIGRUM L. UNDER DIFFERENT GROWTH CRITERIA - Siti Khodijah, Nyayu; Muntoro, Muntoro; Setiawan, Iwan; Nabila, Nabila; Irman, Irman; Vania, Vania (SEAMEO BIOTROP, 2024)
The pepper plant (Piper nigrum L.) is Indonesia's leading spice commodity. Bangka Belitung as a producing center still has problems in cultivation, including nutrient availability. Nutrients N, P and K are macro elements that really determine the growth of plants, including pepper. This research aims to identify the status of macro nutrients, namely N, P and K in pepper plants in Simpang Katis Village, Central Bangka Regency, through observing growth status, leaf visuals, nutrient analysis and plant tissue analysis. This research was carried out in Simpang Katis Village, Central Bangka Regency in July-September 2023. The experimental method used in this research was observation and laboratory analysis methods. The results of the observation data show that NPK nutrients in land with very good growth criteria have N-total of 0.22%, P2O5 available is; 383.2 mg/kg and available K2O of; 6.4 mg/kg. Plant growth with poor growth criteria has a total N content of 0.20%, P2O5 of 115.1 mg/kg and K20 of 7.1 mg/kg. kg. while plant tissue has an N-Total content of 2.41%, P-Total of 0.26 percent and K-total of 2.47 percent for plants with very good growth criteria and N-total, P-total and K-total respectively - respectively .2.79, 0.32 and 3.95 mg/kg for plant tissue with poor growth criteria.